HUBUNGAN KETERAMPILAN MENGAJAR ABAD 21 GURU TERHADAP MOTIVASI BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPAS SD NEGERI BATULACCU KOTA MAKASSAR - Rosdiah Salam; Latri Aras; Putra Mardika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is quantitative research with a correlational type of research which has objectives 1). To find out a picture of the 21st century teaching skills of teachers at Batulaccuu State Elementary School, Makassar City. 2). To find out a picture of student learning motivation at Batulaccu State Elementary School, Makassar City. 3). To find out whether there is a relationship between 21st century teaching skills and student learning motivation at Batulaccu State Elementary School, Makassar City. Variable X in this research is 21st century teaching skills, while variable Y in this research is student learning motivation. The population in this study was 35 students. Data collection was carried out by providing questionnaires and documentation. The power analysis techniques used in this research are descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistics, namely the average value and percentage, a picture of the teacher's 21st century teaching skills and student learning motivation is in the very good category. Then, based on the results of inferential statistical analysis, it shows that tcount is greater than ttable at the 5% significance level. Therefore H0 is rejected and H1 is accepted. From the results of this research, it was concluded that there is a significant relationship between teachers' 21st century teaching skills and student learning motivation at Batlaccu State Elementary School, Makassar City.